Empathy Microblog An Online Tool for Training and Experiencing Empathy - Ossy Dwi Endah Wulansari; Johanna Pirker; Christian Guetl (International Conference on Psychology and Education (ICPE), 2023)
Empathy Online Tool is a tool in the form of online media that is dedicated to being able to understand a person's emotions before and after accessing games and storytelling objects. This study aims to analyse user experience, especially empathy experience in determining the type of media or tool that can stimulate someone's empathy more after accessing an object. The research method used is a quantitative method using the IRI (Interpersonal Reactivity Index) instrument and a qualitative method using an assessment of microblogs written by users. This research produces additional features to the empathy online tool. The assessment in this study consisted of five indicators, namely Affective Reflection, Emotion Wheel, Microblog (Assessor 1 and 2), and IRI Increase. Features have been added in the form of Slider Range and Geneva Emotion Wheel by adding source code to the previously designed program code. Based on the results of the conclusions in this study, men are more stimulated by games, while women are more stimulated by storytelling. The percentage results of the study show that 60% of participants have the same level of empathy experience through playing the game 'Path Out' and accessing storytelling 'Brothers Across Borders'.